Physicochemical properties of MgO-silica fume cementitious materials exposed to high temperatures. (1st June 2022) - Ma, Hongqiang; Zhang, Shaochen; Feng, Jingjing
Abstract: In this paper, MgO and silica fume (SF) are used to prepare MgO-SF cementitious materials, physicochemical properties of MgO-SF materials at room temperature (RT), 100 °C, 200 °C, 300 °C, 400 °C, 600 °C and 800 °C are studied. By means of X-ray diffraction (XRD), fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance ( 29 Si MAS-NMR), mercury intrusion porosimetry (MIP) and scanning electron microscopy-energy spectrometer (SEM-EDS), the changes of cementitious phase are explored to support the strength change results. The research results show that after a high temperature of 800 °C, the residual compressive strength of MgO-SF mortars is between 43.19% and 66.18%, showing excellent high-temperature resistance. XRD, FT-IR and SEM-EDS test results show that M-S-H gel has stronger thermal stability than brucite. The 29 Si MAS-NMR results show that the M-S-H gels at the Q 1 and Q 2 sites turned to the Q 3 site under the action of high-temperature, showing stronger stability. Under the action of high temperature, the presence of MgO-SF undergoes rehydration and M-S-H gel partially decomposes. When the temperature exceeds 400 °C, the brucite loses water and decomposes, the M-S-H gel dehydration and reorganization, and the unhydrated SF particles appear. The gel-like structure, SiO2 and MgO particles are loosely arranged, forming rough and uneven cluster morphology. This study provides an experimental and theoretical basis for the spreading and using MgO-SF materials under high-temperature conditions. Graphical abstract: Image 1 Highlights: (1) The high temperature resistance of MgO-SF (SiO2 ) pastes are studied (2) After high temperature at 800 °C, the residual compressive strength of MgO-SF mortars is between 43.19% and 66.18% (3) M-S-H gel has stronger thermal stability than brucite (4) The ultrasonic velocity and compressive strength shows a weak-positive linearity relationship (5) As the temperature increases, M-S-H gel at Q 1 and Q 2 sites turns to Q 3 site.